Art as revolt : thinking politics through immanent aesthetics - Fancy, David; Skott-Myhre, Hans Arthur (McGill-Queen's University Press, 2019)
"How can we imagine a future not driven by capitalist assumptions about humans and the wider world? How are a range of contemporary artistic and popular cultural practices already providing pathways to post-capitalist futures? Authors from a variety of disciplines answer these questions through writings on blues and hip hop, virtual reality, post-colonial science fiction, virtual gaming, riot grrrls and punk, Raku pottery, post-pornography fanzines, zombie films, and role playing. The essays in Art as Revolt are clustered around themes such technology and the future, aesthetics and resistance, and ethnographies of the self beyond traditional understandings of identity. Using philosophies of immanence--describing a system that gives rise to itself, independent of outside forces--drawn from a rich and evolving tradition that includes Spinoza, Nietzsche, Deleuze, and Braidotti, the authors and editors provide an engrossing range of analysis and speculation. Together the essays, written by experts in their fields, stage an important collective, transdisciplinary conversation about how best to talk about art and politics today. Sophisticated in its theoretical and philosophical premises, and engaging some of the most pressing questions in cultural studies and artistic practice today, Art as Revolt does not provide comfortable closure. Instead, it is understood by its authors to be a "Dionysian machine," a generator of open-ended possibility and potential that challenges readers to affirm their own belief in the futures of this world."--